Sustainable development of islamic banks by creating islamic branding: Challenges, importance, and strategies of islamic branding - Andespa, Roni; Yeni, Yulia Hendri; Fernando, Yudi; Sari, Dessy Kurnia (International Information and Engineering Technology Association, 2024)
This article delves into sustainable growth strategies for Islamic banks, focusing on expanding and developing Islamic branding. Overcoming challenges and outlining an essential strategy, the research, conducted using the PRISMA model, reviews articles from various academic databases. The findings emphasize Sharia compliance as a critical strategy for sustainable development, ensuring strict adherence to Islamic principles in all financial products and services. This approach builds trust within the Muslim community, distinguishing Islamic banks from conventional institutions and establishing a foundation rooted in commitment to Islamic values. The research underscores the ethical principles of Islamic banking, emphasizing risk-sharing and social justice, and highlights the significance of Islamic branding in reinforcing moral foundations and attracting ethically conscious customers. The study highlights how effective branding enhances trust, facilitating financial inclusion and social responsibility. It implies a need for regulatory frameworks supporting standardized Islamic branding, consumer education, and incentives for ethical practices, positioning Islamic banking as a valuable contributor to the financial landscape.